(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
Obstructive diseases of the biliary tract are common clinical problems that frequently present with jaundice, abdominal pain, pruritus, and cholangitis. Accurate identification of the presence, level, and cause of biliary obstruction is essential for appropriate management and treatment planning. Magnetic Resonance Cholangiopancreatography (MRCP) has emerged as a highly reliable, non-invasive imaging modality for evaluating the biliary and pancreatic ductal systems. Over the past decade, and especially between 2020 and 2025, numerous clinical studies have demonstrated the high diagnostic performance of MRCP in detecting choledocholithiasis, biliary strictures, and malignant obstruction. This article reviews the diagnostic capabilities, advantages, limitations, and clinical applications of MRCP in patients with obstructive biliary diseases.